Selected methods of studying a college’s image - Kowalska-Jarnot, Katarzyna (Managerial Economics, 2020)
Positive image and reputation building are important strategies in developing the permanent recognition of a college in the education market. Although it seems challenging to measure image and reputation, they are an important opportunity to gain a competitive advantage due to the fact that they are unique, hard to imitate and increase a college’s chances of attracting more students. Image management requires systematic marketing research. This article is the author’s proposition for a set of image research methods that can be used by colleges.